Pengetahuan Orangtua Tentang Rampan Karies Pada Anak Usia Prasekolah Di PAUD Al-Azhar Desa Cipacing - Putri, Citra Melati; Heriyanto, Yonan; Octaviana, Devy; Putri, Megananda Hiranya (Jurnal Terapi Gigi dan Mulut, 2024)
Rampant caries is a condition in which disease in the hard tissues of the teeth spreads rapidly and affects several teeth at once. This condition is characterized by most or all of the baby teeth being black. The preschool period is considered crucial, because at the age of 2-2.5 years all baby teeth have grown and at the age of 6 years have begun to erupt. The purpose of this study was to determine the level of knowledge of parents of PAUD Al-Azhar students about caries rampant at the age of preschool children and to determine the number of students who experience caries rampant based on patterns. This research method is a descriptive survey that is useful for describing the results of research. The sampling technique used total sampling. Respondents were 21 parents of students and students of PAUD AlAzhar, whose knowledge level was measured and caries rampant was seen. Data analysis was processed statistically and represented in a frequency distribution table using the SPSS application. The results showed that the knowledge of parents of PAUD Al-Azhar students about caries rampant with moderate criteria as much as (57.1%) and 11 students of PAUD Al-Azhar experienced caries rampant (52.4%). The level of knowledge of parents of students with moderate criteria illustrates the cause of the high incidence of caries rampant in children of PAUD Al-Azhar Cipacing Village.